A large-area double rotating-crystal monochromator for time-focusing neutron instruments. (September 2016) - Zanatta, M; Orecchini, A; Aisa, S; Casinini, F; Farnesini, L; Deen, P P; Paciaroni, A; Petrillo, C; Sacchetti, F
Abstract: We present the principle and the first prototypes of a double rotating-crystal monochromator, based on an assembly of smaller rotating elements. Such a device was developed as the key element to implement a parallel-beam modification of the time-focusing technique for neutron spectrometers. This concept is particularly promising for long-pulse sources and can bring specific advantages on continuous sources as well. Neutron tests performed on the first prototypes validate the mechanical reliability of the proposed design and the feasibility of a large-area double rotating-crystal monochromator based on this technology.